"A Constant State of Flex and Change": A Teacher Candidate's Perceptions of and Experiences with Military-Connected Learners - Vicki S. Sherbert (Educational Considerations, 2018)
All teacher candidates enter the classroom with initial perceptions and assumptions regarding their students’ diverse lived experiences and the role those experiences may play in the classroom (Wenger & Dinsmore, 2005). For teacher candidates with no military background, concerns may extend beyond those typical of teacher candidates in other internship placements to include worries about understanding and meeting the unique needs of military-connected learners. This qualitative case study involved three teacher candidates who were about to begin their student teaching internships working in elementary classrooms in schools on a military post. This article will offer an in-depth description of one of the candidates’ experiences. During three interview sessions, Lindsay (pseudonym), a white, female in her early twenties, shared her perceptions of military-connected learners and described her experiences working with them. She was interviewed at the beginning of her internship experience prior to meeting her students, mid-way through the semester, and at the culmination of the internship. She described her own lived experiences, her perceptions of students in general and military-connected students in particular, and her perceptions of the diverse lived experiences of military-connected learners. The phenomenon of her perceptions of military-connected learners and her experiences serving them were examined and described through a sociocultural lens. In this article, background information on military-connected learners and a brief description of sociocultural aspects of identity and agency will be followed by a description of the perceptions and experiences shared by Lindsay throughout her internship. Aspects of identity and agency will be considered as, in her own words, she describes her anxieties, successes, and growth as her identity shifts from a teacher candidate to a professional educator. Insights for teacher educators preparing candidates to work with military-connected learners will be considered.
Keywords: teacher candidates; military-connected learners; identity; agency